Analysis of Social Media Language Trends: A Study of Changes in the Meaning of Contemporary Arabic Words in the Digital Era - Uyuni, Yuyun Rohmatul; Nuroh, Nuroh; Amalia, Novi (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Advances in information technology, especially social media platforms, have affected the dynamics of languages, including Arabic. Through a descriptive linguistic approach, this study examines how the use of Arabic on social media has shifted the meaning of certain words, introduced new terms, and created variations in daily use. Data was collected from various social media platforms, including Twitter, Instagram, TikTok, and Facebook, focusing on words that underwent a change in meaning or the emergence of new terms that were not found in classical Arabic. The data collected analyzed through identification, categorization, and comparison with classical Arabic to understand the change in meaning. Contextual analysis is also carried out by examining the use of words in various situations on social media and the influence of digital culture. The results of this study show that the development of technology and the use of social media have brought changes to the contemporary Arabic language. Some words have experienced a shift in meaning, the addition of new meanings, and adaptation to the digital context. This phenomenon reflects the social and cultural dynamics that are developing in Arab society, especially among the younger generation who are increasingly accustomed to technology.